Transformation of Hryhorii Skovoroda Ideas in Ukrainian Literature of the XX century (some observations) - Атаманчук, В. (Київський національний університет імені Тараса Шевченка, 2022)
The article is devoted to the analysis of the features of the reception of H. Skovoroda's work by Ukrainian writers of the 20th century. In the study, attention is paid to the outlining of the main principles of H. Skovoroda's philosophical concept and the definition of the forms of its artistic embodiment in the works of the outstanding poet and philosofer. The specificity of the subsequent transformation of the philosopher's ideas in Ukrainian literature of the 20s and 60s of the 20th century is traced. It was determined that the artistic work of H. Skovoroda is a unique phenomenon of Ukrainian culture considering that it constitutes the ideological and artistic foundation of all subsequent stages of cultural development. The significance of the figure of H. Skovoroda is outlined, which is determined by the fact that the Ukrainian philosopher and poet managed to represent with his work deep manifestations of inner energy, which nourishes all manifestations of transcendence and is expressed in the form of intuitively recognizable images, ideas, and meanings. It is indicated that the philosophical concept of the outstanding thinker, on the basis of which the worldview and ideological and artistic parameters of the work of many of his successors were formed, consists of many semantic projections that require different levels of perception. First of all, it concerns the reproduction of human relationships with the spiritual world. It is proved that P. Tychyna's collection "Instead of Sonnets and Octaves" testifies to the transformation of H. Skovoroda's idea of inner search, which is manifested in the desire of the lyrical hero of the collection to find harmony in a world that has undergone chaotic transformations. It was determined that the appeal to the image of Skovoroda and artistic reinterpretations of his ideas is observed in the poets of the 60s of the 20th century. The expansion of the external world into infinity in the poems of V. Symonenko, V. Vingranovskyi, and I. Drach was combined with an acute need for internal identification, self-knowledge, which clearly resonates with the philosophical searches of H. Skovoroda.

Присвячено аналізу особливостей рецепції творчості Г. Сковороди українськими письменниками ХХ ст. У дослідженні увага приділена окресленню головних засад філософської концепції Г. Сковороди та визначенню форм її художнього втілення у творах видатного поета і мислителя. Простежується специфіка подальшої трансформації ідей філософа в українській літературі 20-х та 60-х рр. ХХ ст. Проаналізовано характерні риси окремих поетичних творів П. Тичини, В. Симоненка, М. Вінграновського, у яких втілені ідеї, співвідносні зі світосприйняттям українського філософа. Окреслено роль художніх символів у творах названих поетів.
Трансформація ідей Григорія Сковороди в українській літературі ХХ ст. (окремі спостереження)
Keywords: philosophical concept; idea; symbol; image; metaphor; філософська концепція; ідея; символ; образ; метафора